Una verdadera "isla en el nuevo sur". Las donaciones condicionadas en el arroyo Azul durante el rosismo - Lanteri, Sol (Centro de Historia Argentina y Americana, 2007)
In the context of the study of the policy of fiscal lands implemented by Rosas government in Buenos Aires countryside, this work focuses on the modality known as "conditioned donations", that since 1832 became effective only in an area of the south frontier, the Azul stream. So that, we begin establishing the particularities that the settlement process presented, and then we analyze the local impact that the cessions of fiscal lands had during the period 1820- 1860, in order to find out with more precision the importance of donations compared with other grant forms in space occupation and in the structure of the holding of the resource. Finally, in a last section we establish the central characteristics of transactions among private hands, to attain a more accurate definition of the processes involved.